AN ANTHOLOGY OF THE DISTINGUISHED ACHIEVEMENTS IN SCIENCE AND TECHNIQUE. PART 51: ROCKET-SPACE TECHNOLOGY DESIGNER SERGEY KOROLEV AND HIS ACCOMPLISHMENTS IN MISSILE DESIGN - M. I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2019)
Purpose. Preparation of short scientifically-historical essay about one of founders of domestic rocket production and practical cosmonautics, distinguished Soviet designer of space-rocket technology Sergey Pavlovich Korolev. Methodology. Known scientific methods of collection, analysis and analytical treatment of scientific and technical information, touching becoming and development in the world of space-rocket technique and resulted in scientific monographs, journals and internet-reports. Results. A short scientifically-historical essay is presented about the distinguished Soviet designer of space-rocket technique S.P. Korolev, becoming one of founders of domestic rocket production and practical cosmonautics. The important deposit of former German people, creating rockets, workings in the USSR after completion of the World War II is marked, in development of the first Soviet ballistic rockets. Basic scientific and technical achievements of talented and purposeful scientist and practical worker, becoming in 1950 a Chief Designer of the Special Design Bureau No. 1 (SDB-1), S.P. Korolev in area of creation of Soviet strategic rocket weapon (rocket-nuclear «shield») and modern space-rocket technique for mastering of near and distant space tellurians. It is pointed out that under the direction of the Chief Designer of SDB-1 S.P. Korolev in the USSR was developed and accepted on the armament of Soviet Army consisting of two stages intercontinental ballistic rocket (ICBR) of type P-7 (1956, military index 8K71, by power of thermonuclear war-head in 5 Mt and distance of its flight in 8 thousands km) with the liquid rocket engines (LRE) of type РД-107 and РД-108 of design of distinguished Soviet designer in area of rocket engines V.P. Glushko. It is indicated that the Chief Designer S.P. Korolev is the «father» of domestic space-rocket technique, providing by powerful launch vehicles, created in the USSR on the basis of ICBR with LRE of РД-7 type (military index 8K71), start of first in the world of Soviet space satellite (on Octobers, 4, 1957) and start on the circumterrestrial space orbit of the first in history humanity of Soviet cosmonaut Yu.A. Gagarin (on April, 12, 1961). Originality. Certain systematization is executed of known from mass medias of scientific and technical materials, touching becoming and development in the USSR of rocket production, at the sources of which the talented scientist-practical worker and distinguished Soviet designer of space-rocket technique S.P. Korolev. Practical value. Scientific popularization and deepening for the students of higher school, engineer and technical and scientific workers of physical and technical knowledge in area of history of becoming and development in the former USSR of modern rocket production, extending their scientific and technical range of interests and further development of scientific and technical progress in society.